The identity of public health in COVID-19 times - Odone, Anna; Vitale, Marco; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2020)
The COVID-19 hit the world with devastating clinical, economic and social burden.  If any constructive element arises from this tragedy, it is a greater awareness of the key role of public health, which will also be instrumental in the way out of the crisis. Defined in broader terms as the science of protecting the safety and improving the health of communities through education, policy making and research for disease and injury prevention, public health action has guided COVID-19 surveillance and monitoring, the adoption of containment and mitigation measures, has informed the management and organization of  healthcare delivery in emergency and has fuelled health communication and education to the general population. [...]